A modified lithium oxalate, preparation method and application thereof

By uniformly distributing carbon materials and metal oxides in lithium oxalate, modified lithium oxalate was prepared, which solved the existing problems of low electrochemical activity and low decomposition efficiency of lithium oxalate, and achieved improved electrochemical activity, improved decomposition efficiency and scope of application Expanded effect.

CN114300680BActive Publication Date: 2025-02-11EAST CHINA UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111506089.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-10
Publication Date
2025-02-11
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

The existing lithium oxalate has low electrochemical activity, low decomposition efficiency, low application range, and holes generated by decomposition can easily cause poor electrode contact.

Method used

Modified lithium oxalate is prepared by uniformly distributing carbon materials, metal oxides and lithium oxalate, using carbon fibers and/or carbon nanotubes as carbon materials, iron tetraoxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide as metals Oxides improve the electrochemical activity and decomposition efficiency of lithium oxalate.

Benefits of technology

The electrochemical activity of modified lithium oxalate has been greatly improved, the decomposition efficiency has been improved, and the scope of application has been expanded. The carbon dioxide generated by decomposition has been partially dissolved in the electrolyte, inhibiting the decomposition of the electrolyte and improving the flame retardancy and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114300680B_ABST
    Figure CN114300680B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified lithium oxalate, a preparation method and application thereof. The present invention provides a modified lithium oxalate, which comprises a carbon material, a metal oxide and lithium oxalate, wherein the metal oxide is uniformly distributed on the carbon material, and the lithium oxalate is uniformly distributed on the carbon material; the carbon material is carbon fiber and / or carbon nanotube, and the metal oxide is one or more of ferroferric oxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide; the mass ratio of the carbon material to the lithium oxalate is (0.005-0.1):1; the mass ratio of the metal oxide to the lithium oxalate is (0.005-0.1):1. The modified lithium oxalate has high electrochemical activity, high decomposition efficiency and wide application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to modified lithium oxalate, a preparation method and application thereof. Background Art

[0002] Due to the characteristics of the negative electrode material, a solid electrolyte film (SEI film) will be generated on the surface of the lithium-ion full battery during the formation process. This process will consume some of the active lithium ions in the battery, resulting in some irreversible capacity loss of the battery. At present, graphite is mostly used as the negative electrode on the market. The irreversible capacity loss of graphite is generally around 10%, which is acceptable. However, for the next generation of high-energy negative electrode materials such as silicon-carbon negative electrodes or metal oxides, the irreversible capacity loss will reach more than 30%, which will undoubtedly greatly limit the development of the battery industry. However, lithium replenishment technology can eliminate this part of the capacity loss, thereby greatly improving the energy density of the battery. The current lithium replenishment technology is mainly divided into two types: negative electrode lithium replenishment technology and positive electrode lithium replenishment technology. Among them, the negative electrode lithium replenishment technology is mainly divided into two types: electrochemical lithium replenishment and lithium powder lithium replenishment. Among them, electrochemical lithium replenishment requires lithium insertion into the negative electrode material by pre-discharge. The operation is complicated and has extremely high environmental requirements. Therefore, it is generally only suitable for small-scale applications in laboratories. Lithium powder replenishment requires the direct addition of metallic lithium powder during the preparation of the negative electrode slurry. However, since metallic lithium powder is expensive and has great safety risks, the risk of using it in actual production is also extremely high.

[0003] Due to the characteristics of positive electrode lithium supplement materials such as relative stability, low cost, and easy synthesis, they only need to be added to the slurry during the preparation of the positive electrode slurry, and they are also highly operable, so they have received more and more attention in recent years. Among them, lithium oxalate in the positive electrode lithium supplement material has received great attention in recent years due to its high theoretical capacity, water and oxygen stability, and low cost. However, since lithium oxalate is an insulator, its conductivity, ion mobility, and electrochemical activity are very low, resulting in a high decomposition voltage (4.7V) when lithium oxalate is used as a lithium supplement. In addition, the applicable material system of unmodified lithium oxalate is limited, and it can only be decomposed normally in metal oxide positive electrode materials with catalytic activity, and the decomposition efficiency in the lithium iron phosphate system is only about 30%. In addition, the particle size of unmodified lithium oxalate is very large, and after decomposition in the electrode, large holes will be formed in the electrode, which can easily cause problems such as poor contact of the electrode. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the existing lithium oxalate has low electrochemical activity, low decomposition efficiency, low application range, and the holes generated by decomposition easily cause poor electrode contact. To this end, the present invention provides a modified lithium oxalate, a preparation method and application thereof. The modified lithium oxalate has high electrochemical activity, high decomposition efficiency and a wide application range.

[0005] The present invention provides a modified lithium oxalate, which comprises a carbon material, a metal oxide and lithium oxalate, wherein the metal oxide is evenly distributed on the carbon material, and the lithium oxalate is evenly distributed on the carbon material;

[0006] The carbon material is carbon fiber and / or carbon nanotube, and the metal oxide is one or more of ferroferric oxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide;

[0007] The mass ratio of the carbon material to the lithium oxalate is (0.005-0.1):1; the mass ratio of the metal oxide to the lithium oxalate is (0.005-0.1):1.

[0008] In a certain embodiment, the modified lithium oxalate may have a spherical structure.

[0009] In a certain embodiment, the particle size of the spherical structure can be 200nm to 2000nm, or can be 500nm.

[0010] In a certain embodiment, in the modified lithium oxalate, the carbon material is in the form of a three-dimensional network.

[0011] In a certain embodiment, the carbon material may be a carbon material used for structural support.

[0012] In a certain embodiment, the carbon nanotubes may be carboxylated carbon nanotubes and / or multi-walled carbon nanotubes, or multi-walled carbon nanotubes.

[0013] In a certain embodiment, the parameters of the carbon nanotubes may be as follows: diameter 40-60 nm, length ≤ 10 μm.

[0014] In one embodiment, the metal oxide may be metal oxide quantum dots.

[0015] In a certain embodiment, the particle size of the metal oxide may be 1 nm to 5 nm, or may be 3 nm.

[0016] In a certain embodiment, the cobalt tetroxide may be cobalt tetroxide quantum dots.

[0017] In a certain embodiment, the particle size of the cobalt trioxide can be 1 nm to 5 nm, or even 3 nm.

[0018] In one embodiment, the method for preparing the cobalt trioxide quantum dots can be as follows:

[0019] In an alcohol solvent, cobalt salt is reacted with ammonia water to obtain the cobalt tetroxide quantum dots.

[0020] The alcohol solvent is a conventional alcohol solvent for this type of reaction in the art.

[0021] In one embodiment, the alcohol solvent is ethanol.

[0022] In a certain embodiment, the volume molar ratio of the alcohol solvent to the cobalt salt can be (5L-15L):1mol, or can be 10L:1mol.

[0023] The cobalt salt is a conventional cobalt salt for this type of reaction in the art.

[0024] In one embodiment, the cobalt salt may be cobalt acetate.

[0025] In a certain embodiment, the ammonia water may be 25% ammonia water.

[0026] In one embodiment, the NH 3 The molar ratio of the cobalt salt can be (10-15):1, or 14:1.

[0027] The reaction temperature is a conventional temperature for this type of reaction in the art.

[0028] In one embodiment, the reaction temperature can be 80 degrees Celsius.

[0029] In one embodiment, the post-treatment of the reaction may be: adding acetone to the reaction solution.

[0030] In one embodiment, the method for preparing the cobalt trioxide quantum dots can be as follows:

[0031] In ethanol, cobalt acetate is reacted with 25% ammonia water, and then acetone is added to obtain the cobalt tetroxide quantum dots; the volume molar ratio of the ethanol to the cobalt acetate is (5L-15L): 1mol; the NH 3 The molar ratio of the cobalt acetate is (10-15):1; and the reaction temperature is 80 degrees Celsius.

[0032] In a certain embodiment, the mass ratio of the metal oxide to the lithium oxalate may be 0.02:1.

[0033] In a certain embodiment, the mass ratio of the carbon material to the lithium oxalate may be 0.02:1.

[0034] In a certain embodiment, the mass ratio of the carbon material to the metal oxide is (0.2-1):1, or 1:1.

[0035] In a certain embodiment, the modified lithium oxalate may be composed of the carbon material, the metal oxide and the lithium oxalate.

[0036] The present invention also provides a method for modifying lithium oxalate, which comprises the following steps: drying a mixture to obtain modified lithium oxalate; the mixture comprises water, a carbon material, a metal oxide and lithium oxalate;

[0037] The carbon material is carbon fiber and / or carbon nanotube, and the metal oxide is one or more of ferroferric oxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide;

[0038] The mass ratio of the carbon material to the lithium oxalate is (0.005-0.1):1; the mass ratio of the metal oxide to the lithium oxalate is (0.005-0.1):1.

[0039] In one embodiment, the modified lithium oxalate may be as described above.

[0040] In a certain embodiment, the carbon material may be a carbon material used for structural support.

[0041] In a certain embodiment, the carbon nanotubes may be carboxylated carbon nanotubes and / or multi-walled carbon nanotubes, or multi-walled carbon nanotubes.

[0042] In a certain embodiment, the parameters of the carbon nanotubes may be as follows: diameter 40-60 nm, length ≤ 10 μm.

[0043] In one embodiment, the metal oxide may be metal oxide quantum dots.

[0044] In a certain embodiment, the particle size of the metal oxide may be 1 nm to 5 nm, or may be 3 nm.

[0045] In a certain embodiment, the cobalt tetroxide may be cobalt tetroxide quantum dots.

[0046] In a certain embodiment, the particle size of the cobalt trioxide can be 1 nm to 5 nm, or even 3 nm.

[0047] In one embodiment, the method for preparing the cobalt trioxide quantum dots can be as follows:

[0048] In an alcohol solvent, cobalt salt is reacted with ammonia water to obtain the cobalt tetroxide quantum dots.

[0049] The alcohol solvent is a conventional alcohol solvent for this type of reaction in the art.

[0050] In one embodiment, the alcohol solvent is ethanol.

[0051] In a certain embodiment, the volume molar ratio of the alcohol solvent to the cobalt salt can be (5L-15L):1mol, or can be 10L:1mol.

[0052] The cobalt salt is a conventional cobalt salt for this type of reaction in the art.

[0053] In one embodiment, the cobalt salt may be cobalt acetate.

[0054] In a certain embodiment, the ammonia water may be 25% ammonia water.

[0055] In one embodiment, the NH 3 The molar ratio of the cobalt salt can be (10-15):1, or 14:1.

[0056] The reaction temperature is a conventional temperature for this type of reaction in the art.

[0057] In one embodiment, the reaction temperature can be 80 degrees Celsius.

[0058] In one embodiment, the post-treatment of the reaction may be: adding acetone to the reaction solution.

[0059] In one embodiment, the method for preparing the cobalt trioxide quantum dots can be as follows:

[0060] In ethanol, cobalt acetate is reacted with 25% ammonia water, and then acetone is added to obtain the cobalt tetroxide quantum dots; the volume molar ratio of the ethanol to the cobalt acetate is (5L-15L): 1mol; the NH 3 The molar ratio of the cobalt acetate is (10-15):1; the reaction temperature is 80 degrees Celsius.

[0061] In a certain embodiment, the mass ratio of the metal oxide to the lithium oxalate may be 0.02:1.

[0062] In a certain embodiment, the mass ratio of the carbon material to the lithium oxalate may be 0.02:1.

[0063] In a certain embodiment, the mass ratio of the carbon material to the metal oxide is (0.2-1):1, or 1:1.

[0064] In a certain embodiment, the mass concentration of the lithium oxalate in the mixture can be 0.1% to 10%, or can be 0.5%.

[0065] In one embodiment, the drying temperature may be 200°C to 400°C, or 300°C.

[0066] In a certain embodiment, the drying may be atomization drying.

[0067] In a certain embodiment, the atomization drying can be ultrasonic atomization drying and / or spray atomization drying, and can also be ultrasonic atomization drying.

[0068] In a certain embodiment, the parameters of the ultrasonic atomization drying can be a drying temperature of 200°C to 400°C and a carrier gas volume of 5L / min to 20L / min, or a drying temperature of 300°C and a carrier gas volume of 10L / min.

[0069] In a certain embodiment, the mixture may consist of the water, the carbon material, the metal oxide and the lithium oxalate.

[0070] The present invention also provides a modified lithium oxalate, which is prepared according to the above-mentioned lithium oxalate modification method.

[0071] The present invention also provides a use of the modified lithium oxalate as a lithium supplement in a lithium ion battery.

[0072] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0073] The reagents and raw materials used in the present invention are commercially available.

[0074] The positive and progressive effects of the present invention are:

[0075] (1) The lithium oxalate modification process of the present invention is simple, and only requires mixing three solutions and then performing a one-step atomization drying method to obtain the modified lithium oxalate.

[0076] (2) The lithium oxalate prepared by the present invention is small in size, and the modified spherical lithium oxalate has a three-dimensional network structure support with catalytic active units inside. The electrochemical activity of the modified lithium oxalate is greatly improved, and the decomposition voltage is reduced from 4.7V to 4.1V. The applicability of the modified lithium oxalate is enhanced, and it can be normally used in the lithium iron phosphate system.

[0077] (3) The modified lithium oxalate prepared by the present invention has an internal three-dimensional network structure which can improve the stability of the lithium oxalate decomposition process and support the structure, thereby solving problems such as poor contact.

[0078] (4) In the present invention, the carbon dioxide generated by the decomposition of lithium oxalate is not completely discharged from the electrolyte system. Part of the carbon dioxide is dissolved in the electrolyte to inhibit the decomposition of the electrolyte, thereby ensuring the stability of the electrolyte and improving the flame retardancy and stability of the battery system.

[0079] (5) The preparation method of the present invention is low-cost and suitable for mass production. It can be directly used in battery production without upgrading the current lithium-ion battery production equipment to improve battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 The schematic diagram of the synthesis of Example 1 and Comparative Example 1 of the present invention;

[0081] Figure 2 The scanning electron microscope morphology images of Example 1 of the present invention and Comparative Examples 1 and 2;

[0082] Figure 3 X-ray spectra of Example 1 and Comparative Example 1 of the present invention;

[0083] Figure 4 The electrochemical performance comparison diagram of Example 1 of the present invention and Comparative Examples 1 and 2;

[0084] Figure 5 It is the electrochemical performance diagram of comparative example 3;

[0085] Figure 6 This is a performance comparison diagram of Example 1 of the present invention and Comparative Examples 1 and 2 in a lithium iron phosphate electrode;

[0086] Figure 7 This is a comparison chart of the electrochemical performance of silicon-carbon / / lithium iron phosphate full battery with / without adding Example 1;

[0087] Figure 8 This is a morphology characterization diagram of the lithium iron phosphate electrode doped with lithium oxalate after charging. DETAILED DESCRIPTION

[0088] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0089] Example 1

[0090] Example 1 uses modified lithium oxalate prepared by ultrasonic atomization drying, and the specific steps are as follows: The preparation method of cobalt oxide quantum dots is as follows: 0.5g of cobalt acetate is dissolved in 30ml of ethanol, and after it is completely dissolved, 3ml of 25% ammonia water is added, and then the solution temperature is raised to 80 degrees Celsius, and it is kept for 3 hours under stirring and reflux. After the reaction is completed, 100ml of acetone is added to precipitate the quantum dots, and after centrifugation, cobalt oxide quantum dots with a particle size of 3nm can be obtained. The obtained cobalt oxide quantum dots are dissolved in water to obtain a cobalt oxide quantum dot dispersion. After that, 0.5g of unmodified lithium oxalate was dissolved in 100ml of deionized water, and then 1ml of 10mg / ml cobalt trioxide quantum dot dispersion (solvent is water) was slowly added dropwise to the above solution, and after stirring evenly, 1ml of 10mg / ml carbon nanotube dispersion (Aladdin, carbon nanotube aqueous dispersion, 9.5-12.5wt%, diameter 40-60nm, length ≤10μm) was slowly added dropwise to the above solution to finally obtain a precursor solution. Subsequently, the precursor solution was atomized under the action of an ultrasonic atomizer, and then sent to a 300°C dryer at an air flow rate of 10L / min to finally obtain modified lithium oxalate.

[0091] Figure 1 This is a schematic diagram of the synthesis of Example 1 of the present invention: Precursor solution droplets enter a high-temperature drying chamber under the load of airflow, and then the modified lithium oxalate can be collected at the collection end.

[0092] Comparative Example 1

[0093] Comparative Example 1 and Example 1 adopt the same method, the only difference being that no carbon nanotube dispersion is added.

[0094] Figure 1 It is a schematic diagram of the synthesis of comparative example 1 of the present invention: the precursor solution droplets enter the high-temperature drying chamber under the load of airflow, and then the modified lithium oxalate can be collected at the collection end.

[0095] Comparative Example 2

[0096] Comparative Example 2 is commercial unmodified lithium oxalate.

[0097] Comparative Example 3

[0098] Comparative Example 3 shows the effects of commercial cobaltous oxide, manganese-rich oxide, ferrous oxide and nickel monoxide on the decomposition efficiency of commercial unmodified lithium oxalate.

[0099] Effect Example 1 The modified lithium oxalate materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were characterized by SEM and X-ray diffraction.

[0100] Figure 2The scanning electron microscope morphology of Example 1, Comparative Example 1 and Comparative Example 2 shows that the particle size of Example 1 is smaller, only about 500nm, while the diameter of Comparative Example 1 is about 2μm. This is because the added carbon nanotubes refine the droplets of the precursor. The unmodified commercial lithium oxalate in Comparative Example 2 has a very irregular morphology, a particle size of about 10μm, and severe agglomeration.

[0101] Figure 3 The X-ray spectra of Example 1 and Comparative Example 1 show that the material of Example 1 has good crystallinity and no peak of cobalt tetroxide is observed, indicating that the quantum dots are evenly distributed inside the material. The material of Comparative Example 1 has poor crystallinity and a peak of cobalt tetroxide is observed, indicating that the quantum dots agglomerated during the drying process.

[0102] Effect Example 2 The modified lithium oxalate materials obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were subjected to constant current charging test

[0103] Here are the steps:

[0104] The modified lithium oxalate, Ketjen black and polyvinylidene fluoride were added to 1-methyl-2-pyrrolidone in a ratio of 7:2:1, and a black viscous slurry was obtained after grinding. The slurry was applied to aluminum foil and dried to obtain a lithium oxalate electrode sheet. Then, the metal lithium, the diaphragm and the lithium oxalate electrode sheet were assembled into a button battery. The button battery model used was CR2032, the diaphragm model was 2500, and the electrolyte was 1 mol / L lithium hexafluorophosphate solution (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1). After assembly, the battery was removed from the glove box and tested on the Land test system after standing at 30°C for 12 hours. The test operating voltage range was 2.5-4.2V, and the charge and discharge current was 0.5C.

[0105] The results are as follows:

[0106] Figure 4 The constant current charge and discharge performance tests of Example 1, Comparative Example 1 and Comparative Example 2 show that the decomposition voltage of the unmodified lithium oxalate Comparative Example 2 is very high, reaching 4.7V, and the decomposition efficiency at a current density of 0.5C is also very low, only 5.2%. The electrochemical activity of the modified lithium oxalate Example 1 is greatly improved, and its decomposition voltage is reduced to 4.1V, and the decomposition efficiency is increased to 99.8%. Although the decomposition voltage of Comparative Example 1 has also decreased significantly, due to its oversized size, the macropores generated by its decomposition in the electrode cause poor contact, thus causing a sharp drop in voltage.

[0107] Figure 5The effect of commercial cobalt oxide, manganese oxide, ferric oxide and nickel oxide on the decomposition efficiency of commercial unmodified lithium oxalate. It can be seen that nickel monoxide has the weakest catalytic effect on commercial lithium oxalate, and the decomposition voltage only drops from 4.7V to about 4.6V, and the decomposition efficiency is also very low, only 41.69%. Unlike nickel monoxide, the catalytic performance of ferric oxide, manganese oxide and cobalt oxide systems is significantly higher, with decomposition efficiencies of 77.55%, 70.79% and 86.53% respectively, and their decomposition voltages have a significant decline in the middle of charging, among which the decomposition voltage of cobalt oxide drops the most, reaching 4.2V. This experiment shows that among several common metal oxide systems, cobalt oxide has the best catalytic performance.

[0108] Effect Example 3 Half-cell / full-cell performance test of modified lithium oxalate electrodes obtained by adding lithium iron phosphate to Example 1, Comparative Example 1, and Comparative Example 2

[0109] Here are the steps:

[0110] 72 mg of lithium iron phosphate, 8 mg of the obtained modified lithium oxalate, 10 mg of Ketjen black, and 10 mg of polyvinylidene fluoride were added to 1-methyl-2-pyrrolidone respectively, and a black viscous slurry was obtained after grinding. The slurry was applied on an aluminum foil, and after drying, a positive electrode sheet containing lithium oxalate was obtained;

[0111] The metal lithium, the separator and the prepared positive electrode sheet were assembled into a button cell. The button cell model used was CR2032, the separator model was 2500, and the electrolyte was 1 mol / L lithium hexafluorophosphate solution (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1). After assembly, the battery was removed from the glove box and left to stand at 30°C for 12 hours before being tested on the Land test system. The test operating voltage range was 2.5-4.2V, and the charge and discharge current was 0.5C.

[0112] The full-cell assembly method is similar to the half-cell assembly method mentioned above, the only difference is that the metallic lithium is replaced with a silicon-carbon electrode.

[0113] The results are as follows:

[0114] Figure 6 The electrochemical performance test after adding Example 1, Comparative Example 1 and Comparative Example 2 into lithium iron phosphate electrode (half-cell) shows that the decomposition efficiency of unmodified lithium oxalate (Comparative Example 2) in lithium iron phosphate is only 34.2%, while the decomposition efficiency of modified lithium oxalate (Example 1) reaches 99.1%. This shows that the modified lithium oxalate can also be used normally in the lithium iron phosphate system, indicating that the modified lithium oxalate has a wider application range and is therefore more practical.

[0115] Figure 7 The electrochemical performance of the full cell with and without addition of Example 1. Figure 7 (a) is the full battery performance without adding Example 1. It can be seen that the first cycle capacity loss of the battery without adding Example 1 reaches 79.6 mAh g -1 .and Figure 7 (b) is the full battery performance with 10% of Example 1 added, and it can be seen that the first cycle capacity loss is completely compensated. Figure 7 (c) is a comparison chart of the cycle performance of the two batteries. It can be seen that the full battery with Example 1 added did not have the problem of continuous capacity decay in the first 20 cycles. This is because the carbon dioxide produced by the decomposition of lithium oxalate modified the solid electrolyte membrane, thereby improving the cycle stability of the battery. The decomposition of ordinary lithium oxalate can also produce carbon dioxide, but the ordinary decomposition efficiency is very low and cannot be completely decomposed. The decomposition efficiency in the lithium iron phosphate system is only 30%, so the output CO 2 rare.

[0116] Figure 8 The morphology of Example 1 monomer and Example 1 doped with lithium iron phosphate electrode and charged (half-cell) is characterized. The holes with a diameter of about 500nm in the right picture are left after Example 1 is completely decomposed. Only carbon nanotubes are observed in the holes left after decomposition, indicating that Example 1 is completely decomposed. The carbon nanotubes play a supporting role in the holes, which can improve the conductivity of the electrode.

[0117] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for modifying lithium oxalate, characterized in that: The method comprises the following steps: drying the mixture to obtain modified lithium oxalate; the mixture comprises water, carbon material, metal oxide and lithium oxalate; The carbon material is carbon fiber and / or carbon nanotube, and the metal oxide is one or more of ferroferric oxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide; The mass ratio of the carbon material to the lithium oxalate is (0.005-0.1):1; the mass ratio of the metal oxide to the lithium oxalate is (0.005-0.1):

1.

2. The method for modifying lithium oxalate according to claim 1, characterized in that: It meets one or more of the following conditions: a) The carbon material is a carbon material used for structural support; b) the carbon nanotubes are carboxylated carbon nanotubes and / or multi-walled carbon nanotubes; c) The parameters of the carbon nanotubes are as follows: diameter 40-60 nm, length ≤10 μm; d) the metal oxide is a metal oxide quantum dot; e) the particle size of the metal oxide is 1 nm to 5 nm; f) the mass ratio of the metal oxide to the lithium oxalate is 0.02: 1; g) the mass ratio of the carbon material to the lithium oxalate is 0.02: 1; h) the mass ratio of the carbon material to the metal oxide is (0.2-1):1; i) the mass concentration of the lithium oxalate in the mixture is 0.1% to 10%; j) the mixture consists of the water, the carbon material, the metal oxide and the lithium oxalate; k) The drying temperature is 200°C to 400°C; 1) The drying is atomization drying.

3. The method for modifying lithium oxalate according to claim 2, characterized in that: It meets one or more of the following conditions: m) the carbon nanotubes are multi-walled carbon nanotubes; The cobalt tetroxide is cobalt tetroxide quantum dots; the preparation method of the cobalt tetroxide quantum dots can be as follows: in ethanol, cobalt acetate is reacted with 25% ammonia water, and then acetone is added to obtain the cobalt tetroxide quantum dots; the volume molar ratio of the ethanol to the cobalt acetate is (5 L~15 L):1 mol; the molar ratio of NH3 in the ammonia water to the cobalt acetate is (10~15):1; the reaction temperature is 80 degrees Celsius; n) the particle size of the metal oxide is 3 nm; o) the mass ratio of the carbon material to the metal oxide is 1:1; p) the mass concentration of the lithium oxalate in the mixture is 0.5%; q) the drying temperature is 300°C; r) The atomization drying is ultrasonic atomization drying and / or spray atomization drying.

4. The method for modifying lithium oxalate according to claim 3, characterized in that: The parameters of the ultrasonic atomization drying are: drying temperature 200°C~400°C, carrier gas volume 5 L / min~20 L / min.

5. The method for modifying lithium oxalate according to claim 3, characterized in that: The parameters of the ultrasonic atomization drying are: drying temperature of 300°C and carrier gas volume of 10 L / min.

6. A modified lithium oxalate, characterized in that: It is prepared according to the modification method of lithium oxalate as described in any one of claims 1 to 5.

7. The modified lithium oxalate according to claim 6, characterized in that: It comprises a carbon material, a metal oxide and lithium oxalate, wherein the metal oxide is evenly distributed in the carbon material, and the lithium oxalate is evenly distributed in the carbon material; The carbon material is carbon fiber and / or carbon nanotube, and the metal oxide is one or more of ferroferric oxide, manganese tetraoxide, cobalt tetraoxide and nickel monoxide; The mass ratio of the carbon material to the lithium oxalate is (0.005-0.1):1; the mass ratio of the metal oxide to the lithium oxalate is (0.005-0.1):

1.

8. The modified lithium oxalate according to claim 7, characterized in that: It meets one or more of the following conditions: s) The modified lithium oxalate has a spherical structure; t) In the modified lithium oxalate, the carbon material is in a three-dimensional network shape; u) The carbon material is a carbon material used for structural support; v) the carbon nanotubes are carboxylated carbon nanotubes and / or multi-walled carbon nanotubes; w) The parameters of the carbon nanotubes are as follows: diameter 40-60 nm, length ≤10 μm; x) the metal oxide is a metal oxide quantum dot; y) the particle size of the metal oxide is 1 nm to 5 nm; z) the mass ratio of the metal oxide to the lithium oxalate is 0.02: 1; aa) The mass ratio of the carbon material to the lithium oxalate is 0.02: 1; bb) the mass ratio of the carbon material to the metal oxide is (0.2-1):1; cc) The modified lithium oxalate is composed of the carbon material, the metal oxide and the lithium oxalate.

9. The modified lithium oxalate according to claim 8, characterized in that: It meets one or more of the following conditions: dd) The particle size of the spherical structure is 200 nm to 2000 nm; ee) the carbon nanotubes are multi-walled carbon nanotubes; ff) The cobalt tetroxide described is cobalt tetroxide quantum dots; gg) the particle size of the metal oxide is 3 nm; hh) The mass ratio of the carbon material to the metal oxide is 1:

1.

10. The modified lithium oxalate according to claim 9, characterized in that: It meets the following conditions: ii) The preparation method of the cobalt tetroxide quantum dots is as follows: in an alcohol solvent, a cobalt salt is reacted with ammonia water to obtain the cobalt tetroxide quantum dots.

11. The modified lithium oxalate according to claim 10, characterized in that: It meets the following conditions: jj) In ethanol, cobalt acetate is reacted with 25% ammonia water, and then acetone is added to obtain the cobalt tetroxide quantum dots; the volume molar ratio of the alcohol solvent to the cobalt salt is (5 L~15 L):1 mol; the molar ratio of NH3 in the ammonia water to the cobalt salt is (10~15):1; the reaction temperature is 80 degrees Celsius.

12. Use of the modified lithium oxalate according to any one of claims 6 to 11 as a lithium supplement in a lithium ion battery.

Citation Information

Patent Citations

  • Composite material-coated core-shell positive electrode material, preparation method thereof and application in lithium ion battery

    CN107845786A